Study of Economic development for Mobile Banking in India - Dayma, Veejay (2010)
The banking industry has shown tremendous growth in volume and complexity during the last few decades. However there have been concerns that banks have not been able to provide basic banking facilities to vast population, especially the rural population of India. The reasons could be lack of infrastructure and literacy rate to adapt to modern technology. Efforts are being made as financial inclusions can truly lift the financial conditions of rural India. Off-recently mobile phones as a delivery channel for extending banking services have been attaining greater significance. According to Gartner Mobile device sales in India are forecast to reach 138.6 million in 2010, an increase of 18.5 percent over 2009 sales of 117 million units. The rapid growth in users and wider coverage of mobile phone networks have made this channel an important platform for extending banking services to customers.